Large-scale phylogenetic analysis of Amorphophallus (Araceae) derived from nuclear and plastid sequences reveals new subgeneric delineation. (4th May 2017) - Claudel, Cyrille; Buerki, Sven; Chatrou, Lars W.; Antonelli, Alexandre; Alvarez, Nadir; Hetterscheid, Wilbert
Abstract: Remarkably little is known about the evolution of the emblematic genus Amorphophallus . To shed new light on phylogenetic relationships between species of Amorphophallus and test its current classification, the first well-sampled molecular phylogenetic analysis is presented here, comprising 157 species for which we generate nuclear ( ITS1 ) and plastid ( rbcL and matK ) sequences. Our combined plastid and nuclear maximum likelihood and Bayesian inferences provide a solid backbone for subgeneric delineation in supporting the existence of four major clades. These latter clades are here formally recognized as subgenera (two of which are new): Amorphophallus, Metandrium, Scutandrium and Afrophallus . Each subgenus is discussed based on selected morphological features and additional traits (e.g. distribution). Finally, our results strongly support the inclusion of the genus Pseudodracontium in Amorphophallus and the required taxonomic changes are proposed here. In addition to clarifying species relationships in Amorphophallus and proposing a new infrageneric classification, this study provides a baseline for researchers working on the evolution and biogeography of Araceae and more broadly on the tropical flora, especially in Southeast Asia.